Analisis Kepraktisan dan Efektivitas : Penerapan Media Pembelajaran Diferensiasi Konten Dengan Google sites pada Materi Jaringan Komputer - Sujarno, Nonot; Ekohariadi, I.G.P.; Sondang Sumbawati, Meini; Budi Prihanto, Junaidi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The purpose of this study is to find out the extent of the effectiveness and practicality of Google sites as a differentiated learning medium compared to power point media in improving student learning outcomes. This research uses a Research (R&D) approach based on the ADDIE framework. The research subjects were students of class X DKV (Experiment) and Accounting (Control) at SMK Negeri Margomulyo. Data were collected by means of interviews, observations, questionnaires, and assessment of learning outcomes to show that the two elements of analysis could show the correctness of the research hypothesis, so this study was conducted. focus on practicality tests and media effectiveness tests. The results of this study show from the feasibility test, namely the results of media expert validation obtained a score of 92%, material expert validation obtained a score of 90%, and linguist validation obtained a score of 93%. Meanwhile, the learning results of the average score of the pre-test test and the post-test in both classes showed differences. In the control class, the pre-test score was 46 and the test post was 58, while in the experimental class, the pre-test score was 49, the test post score was 69. Meanwhile, the results of the media practicality test obtained a score of 89% and the results of the effectiveness test obtained a score of 88%. From the above data, it can be concluded that there is a significant difference between the learning outcomes of the experimental class and the control class. From the two analyses above, it is clear that the use of Google sites learning media is very practical and effective compared to Power Point learning media judging from the learning outcomes achieved by students.